Community Empwerment by Utilizing Carrots Into Environmentally Friendly Solid Soap - Waloejo, Budi Sugiarto; Agustin, Imma Widyawati; Meidiana, Christia; Sutikno, Fauzul Rizal; Ferly, Ricky Ananda; Saragih, Erica Renata; Irwanto, Natasya Abigail (Fakultas Teknik, Universitas Brawijaya, 2026)
This community service activity aims to empower the community of Rampal Celaket Village, Malang City through training in making solid soap based on carrot extract (Daucus carota L.) which is rich in β-carotene and natural antioxidants. The implementation method was carried out through a participatory approach involving 25 PKK women as the main participants, including field survey stages, material presentations, and practical demonstrations of soap making using the cold process method. The soap making process is carried out by extracting fresh carrots, mixing them with coconut oil, palm oil, olive oil, and sodium hydroxide (NaOH) through saponification reactions, then molded and undergoing a curing process for 3-5 weeks. The results of the activity showed high enthusiasm from participants with a satisfaction rate of 96% and 100% motivation to develop skills further, and the soap products produced had good quality with yellowish orange color, solid texture, fresh aroma, and did not cause skin irritation. This program successfully opened new economic opportunities for the community with attractive profit margins, while increasing awareness of the use of environmentally friendly natural skin care products and supporting women's empowerment in developing micro-enterprises based on local potential.